Effect of the composition of a biologically active dietary supplement with macrofungi mycelia on its antioxidant activity - Krupodorova, T.; Butkevych, T.; Barshteyn, V.; Sevindik, M.; Popovych, V.; Polova, Z. (Regulatory Mechanisms in Biosystems, 2024)
The global demand for macrofungi is driven by their rich content of biologically active substances and trends such as the need for natural medicines, the growing popularity of vegan diets, increased consumer interest in therapeutic and prophylactic dietary supplements, and the expanding use of fungi in the food, pharmaceutical, and cosmetic industries. The aim of this study was to investigate the effect of the composition of a biologically active dietary supplement based on a mixture of macrofungal mycelium on the total phenolic content and antioxidant activity of the supplement. The mycelium of Fomitopsis pinicola, Pleurotus ostreatus and Trametes versicolor were obtained through controlled submerged static cultivation on suitable media. The powdered mycelia of F. pinicola, P. ostreatus, and T. versicolor, which are cubic and plate-shaped conglomerates with rounded edges, translucent, with a smooth surface, were mixed with excipients and granulated. Pharmacotechnological characteristics such as compressibility, powder flowability, moisture content, as well as dosage uniformity and disintegration time of hard capsules significantly varied depending on the granulate composition. The total phenolic content and antioxidant activity of each mycelium and their mixture, as well as of the selected granulates, were determined. Differences in the total phenolic content and antioxidant activity of each mycelium and their mixture were insignificant. Determination of these parameters and the pharmacotechnological parameters of the granulates allowed the identification of the most suitable excipients: lactose monohydrate (5%), mannitol:microcrystalline cellulose 101 in the ratio 2:1 (10%), sodium croscarmellose (1%), and a 0.7% solution of carboxymethyl cellulose (4%). This mixture contains 29.83 ± 0.49 mg GAE/g of total phenolic content and can neutralize the DPPH free radical scavenging by 86.53 ± 0.62%. The obtained results of the study confirm the prospects of using macrofungi mycelium of F. pinicola, P. ostreatus, and T. versicolor as a promising raw material for the development of a new dietary supplement with antioxidant activity.